Respuesta :
[tex]x\dfrac{\mathrm dy}{\mathrm dx}-y=x^2\sin x[/tex]
Divide both sides by [tex]x^2[/tex]. In doing so, we force any possible solutions to exist on either [tex](-\infty,0)[/tex] or [tex]\boxed{(0,\infty)}[/tex] (the "positive" interval in such a situation is usually taken over the "negative" one) because [tex]x[/tex] cannot be 0 in order for us to do this.
[tex]\dfrac1x\dfrac{\mathrm dy}{\mathrm dx}-\dfrac1{x^2}y=\sin x[/tex]
Condense the left side as the derivative of a product, then integrate both sides and solve for [tex]y[/tex]:
[tex]\dfrac{\mathrm d}{\mathrm dx}\left[\dfrac yx\right]=\sin x[/tex]
[tex]\dfrac yx=\displaystyle\int\sin x\,\mathrm dx[/tex]
[tex]\boxed{y=Cx-x\cos x}[/tex]
The general solution of a differential equation is to write y as a function of x.
- The general solution of [tex]x \frac{dy}{dx} - y = x^2 \sin(x)[/tex] is [tex]y = -x\cos(x) + cx[/tex].
- The interval of the solution is [tex](0, \infty)[/tex]
Given
[tex]x \frac{dy}{dx} - y = x^2 \sin(x)[/tex]
Divide through by x
[tex]\frac{x}{x} \frac{dy}{dx} -\frac{y}{x} = \frac{x^2}{x} \sin(x)[/tex]
[tex]\frac{dy}{dx} -\frac{y}{x} = x \sin(x)[/tex]
Let P be function of x. Such that:
[tex]P(x) = -\frac 1x[/tex]
So, we have:
[tex]\frac{dy}{dx} +yP(x) = x\sin(x)[/tex]
Calculate the integrating factor I(x).
So, we have:
[tex]I(x) = e^{\int P(x) dx[/tex]
Substitute [tex]P(x) = -\frac 1x[/tex]
[tex]I(x) = e^{\int-\frac 1x dx[/tex]
Rewrite as:
[tex]I(x) = e^{-\int\frac 1x dx[/tex]
Integrate
[tex]I(x) = e^{-\ln(x)[/tex]
[tex]I(x) = \frac 1x[/tex]
So, we have:
[tex]\frac{dy}{dx} -\frac{y}{x} = x \sin(x)[/tex]
[tex][\frac{dy}{dx} -\frac{y}{x}] \frac 1x = [x \sin(x)] \frac 1x[/tex]
[tex][\frac{dy}{dx} -\frac{y}{x}] \frac 1x =\sin(x)[/tex]
Introduce [tex]I(x) = \frac 1x[/tex].
So, we have:
[tex]\frac{d}{dx}(\frac yx) = \sin(x)[/tex]
Multiply both sides by dx
[tex]d(\frac yx) = \sin(x)\ dx[/tex]
Integrate with respect to x
[tex]\frac yx = -\cos(x) + c[/tex]
Multiply through by x
[tex]y = -x\cos(x) + cx[/tex]
So, the general solution is: [tex]y = -x\cos(x) + cx[/tex], and the interval is [tex](0, \infty)[/tex]
Read more about general solution of a differential equation at:
https://brainly.com/question/4537000